Tailoring the spectral response of a dogbone doublet metamaterial. Issue 6 (June 2016) - Sarin, V. P.; Pradeep, Anju; Jayakrishnan, M. P.; Chandroth, Aanandan; Mohanan, P.; Kesavath, Vasudevan
ABSTRACT: The detailed experimental and simulation studies of the stacked dogbone metamaterial particles are presented in this article. Besides the conventional left handed propagation mode, it is observed that the structure supports Fabry–Perot resonant modes and the excitation of this mode can be identified from the right handed resonant tunnel band in the dispersion diagrams. It is shown that the coupling between the Fabry–Perot and left handed resonant modes gives flat tunnel band characteristics in the dispersion diagram and is associated with huge electromagnetic absorption. The spectral response can be tailored by varying the stacking thickness of the sample making it suitable for microwave absorption and left handed transmission applications. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1347–1353, 2016